2010
DOI: 10.1051/epjconf/20100605006
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of fibre-reinforced composites improved with nanofibres or nanotubes

Abstract: Abstract.A review is presented on the testing and mechanical properties of continuous fibre reinforced composites modified with nanotubes or nanofibres either dispersed in the resin or grown on the microfibres. The nano-level cross-links are shown to be able to (1) increase the fibre/matrix interfacial strength, (2) reduce the inter-fibre crack growth, and (3) improve the inter-ply delamination resistance. A positive influence on the thermal expansion is also detected. However, for unfavourable material consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(120 reference statements)
0
0
0
Order By: Relevance
“…The latter method can employ, e.g., the catalytic decomposition of a hydrocarbon gas over metal particles introduced into the fabric [1]. Both methods have their merits and demerits [2], e.g., significantly higher viscosity of nano-modified resin or potential migration of in situ grown CNFs into air (hardly possible if they are mixed with resin).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter method can employ, e.g., the catalytic decomposition of a hydrocarbon gas over metal particles introduced into the fabric [1]. Both methods have their merits and demerits [2], e.g., significantly higher viscosity of nano-modified resin or potential migration of in situ grown CNFs into air (hardly possible if they are mixed with resin).…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the case, the nano-particles are expected (1) to increase the fibre/matrix interfacial strength, (2) to reduce the matrix cracking, and (3) to improve the delamination resistance. Amongst the mechanical tests able to validate these effects, the DCB test seems to be the most preferable [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for mode II fracture toughness, it was reported that the addition of 7.5% CNFs or 2wt% of CNTs showed significant improvement in mode II fracture toughness. The hardness index showed an improvement of 15% which was consistent throughout the publications (Koysin et al 2010). Greef et al (2011) investigated the effect of adding carbon nanotubes (CNTs) on the damage evolution in a woven carbon fiber/epoxy composite under quasi static tensile loading.…”
Section: Objectivessupporting
confidence: 80%
“…Proceedings of the International Conference on Industrial Engineering and Operations Management Istanbul, Turkey, March 7-10, 2022 2. Literature Review Koysin et al (2010) reviewed the effect of continuous fiber reinforced composites modified with nanotubes or nanofibers on the mechanical properties. The nanofibers were either dispersed in the resin or grown on microfibers.…”
Section: Objectivesmentioning
confidence: 99%